1992
DOI: 10.1080/15287399209531633
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of benzene exposure for the Pliofilm (rubberworker) cohort (1936–1976)

Abstract: The Pliofilm cohort is the most intensely studied group of workers chronically exposed to benzene. Information on this cohort has been the basis for regulations and/or guidelines for occupational and environmental exposure to benzene. Rinsky et al. (1986, 1987) and Crump and Allen (1984) developed different approaches for reconstructing the exposure history of each member of the group. The predicted levels of exposure, combined with the data on the incidence of disease, have been used to estimate benzene's car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 28 publications
0
69
0
1
Order By: Relevance
“…Therefore, an estimate of the concentration of the contaminant on the skin can only be assessed subjectively at present, using the concentration of the contaminant in the source or on contaminated surfaces as an estimate of the concentration of the hazardous substance on the skin. Information about the concentration of the contaminant in the source can be retrieved historically, at least in certain occupational settings, as was shown in two epidemiologic studies (21,25). Retrospective exposure assessment studies should therefore attempt to collect as much information as possible about the concentration of the active ingredient in the source(s) or on contact surface(s) over time, together with information about the actual mass of the contaminant on the skin.…”
Section: Concentration or Mass Of The Contaminantmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an estimate of the concentration of the contaminant on the skin can only be assessed subjectively at present, using the concentration of the contaminant in the source or on contaminated surfaces as an estimate of the concentration of the hazardous substance on the skin. Information about the concentration of the contaminant in the source can be retrieved historically, at least in certain occupational settings, as was shown in two epidemiologic studies (21,25). Retrospective exposure assessment studies should therefore attempt to collect as much information as possible about the concentration of the active ingredient in the source(s) or on contact surface(s) over time, together with information about the actual mass of the contaminant on the skin.…”
Section: Concentration or Mass Of The Contaminantmentioning
confidence: 99%
“…The algorithm included the application method (tractor-or boom-, backpack-, bike-spraying), the method of mixing and loading (direct tank filling, pouring, or scooping), the method of bulb disinfection (manual or mechanical dipping), the application rate (milligrams per hectare), the bulb acreage (hectares), the number of applications, the number of bulbs disinfected per year (number of containers), and a protection factor for personal protective equipment (range: 0 = no protection to 1 = complete protection) (24). In a study of Pliofilm™ workers, exposure to benzene was calculated on the basis of the concentration of benzene in the cement being used, the number of skin contacts with the cement per day, the surface area of the contacted skin (square centimeters), and the contact time (hours per day) (25)(26)(27). Dermal uptake (milligrams per kilogram per day) was subsequently calculated using these dermal exposure estimates, the dermal absorption rate (milligram per square centimeter per hour), and body weight of the individual (kilograms).…”
Section: Quantitative Estimatesmentioning
confidence: 99%
“…This difficulty in validating a risk assessment holds even for a relatively well-studied contaminant with extensive human epidemiologic data, such as benzene. For benzene, the underlying exposure assessment components of the risk assessments arguably remain in debate, with the Pliofilm benzene-exposed cohort the subject of at least 4 distinct exposure assessments (Rinsky et al 1987;Paustenbach et al 1992;Crump 1996;Williams & Paustenbach 2003).…”
Section: Miyazaki Prefecture Outbreakmentioning
confidence: 99%
“…Thus, their estimated value at the early stage (TLV at that time= 100 ppm) was higher than that estimated by Rinsky et al 51 . Meanwhile, Paustenbach et al 103) estimated exposure levels considering that unusually long working hours were practiced in the 1940s, the exposure during this period might be underestimated due to the lack of sufficient measurement apparatus, and that considerable amounts of benzene must have been absorbed through the skin under the working conditions at that time. In comparison to the estimates of Paustenbach et al, it may be concluded that those of Rinsky et al underestimated the benzene exposure in almost all workers, and those of Crump and Allen overestimated the exposure in some job categories and underestimated in others.…”
Section: Biological Monitoring Of Benzene Exposurementioning
confidence: 99%